Deaths and cardiac arrests during anesthesia – An analysis of 361,152 procedures in a major US health system - Basavana Goudra; Arjun Guthal; Kumar Belani (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: The aim was to analyze the factors associated with intraoperative cardiac arrests at a major US academic center. Material and Methods: In this single-center university hospital setting retrospective study, perioperative cardiac arrest data obtained from the clinical quality improvement and local registry from June 1, 2013 to November 19, 2019 was analyzed. Descriptive statistics were used to analyze the findings. Results: A total of 361,152 anesthesia-requiring procedures were performed. At least 49 cardiac arrests occurred in the operating room (at a rate of 1.3 cardiac arrests for every 10,000 surgeries), of which 23 resulted in death (at a rate of 0.6 deaths for every 10,000 surgeries). Twenty-eight cardiac arrests occurred during elective procedures and the remaining were emergencies. Among the causes, hyperkalemia was seen as a likely contributory cause in six patients. PEA (Pulseless electrical activity) was the dominant rhythm and often did not precede other life-threatening arrhythmias. In terms of subspecialty, cardiac surgery witnessed the highest number of cardiac arrests followed by solid organ transplant. Nurse anesthetist/physician anesthesiologist team-delivered care was associated with intraoperative cardiac arrests, with a rate similar to that of all-physician care teams (21 vs. 28), and the death rates were similar (11 vs. 12). Highest number of cardiac arrests belonged to American Society of Anesthesiologists (ASA) 3 category. All patients who sustained cardiac arrests in ASA 2 category also died. Patients with a BMI >30.0 had the highest number of cardiac arrests, although the number of deaths was low. Conclusions: Hyperkalemia is a major factor in intraoperative cardiac arrests. Majority of the cardiac arrests occur during emergency procedures. Solid organ transplant and cardiac surgery carry the highest risk of cardiac arrests.